the development of tax policies and education, as well as to contribute to improving tax compliance within state-owned enterprises, especially PT Pos Indonesia (Persero) Gunungsitoli. - Julianto Laia; Livenasehati Giawa; Sozanolo Lase (Worksheet : Jurnal Akuntansi, 2026)
Analyze influence of tax knowledge, tax awareness, also rational attitude on tax compliance employees at PT Pos Indonesia (Persero) Gunungsitoli. Importance of employee compliance in fulfilling tax obligations, as reflected in the employee’s SPT reporting rates over the past five years. Quantitative approach with primary data obtained through questionnaires distributed to employees of PT Pos Indonesia (Persero) Gunungsitoli. Tax knowledge, tax awareness, also rational attitude have positive significant effect both partially and simultaneously on tax compliance of employees. Good tax knowledge encourages understanding and fulfillment of tax obligations, while tax awareness increases employees’ motivation to comply. Rational attitude also plays a role in employees’ decision-making related to tax reporting. These findings emphasize that improving tax knowledge and awareness, as well as fostering a positive rational attitude, are crucial in promoting employee compliance with tax obligations. This study is expected to serve as a reference for the development of tax policies and education, as well as to contribute to improving tax compliance within state-owned enterprises, especially PT Pos Indonesia (Persero) Gunungsitoli.